(3GdfehPL GdeMGSHj GdeYGUQ ef GdeHGOF Edi GdeYGjjQ (B:s (3OQGSI eYebI aj fXQjI GdeMGSHI (B/s - (3MfGf, QVhGf MdhIs ((3YeGf(B: s (3OGQ hGFd ddfTQ hGdJhRjY(B, s, 2003)
(3fHPI Yf JWhQ Yde GdeMGSHI heMGhdGJ GdJfXjQ GdeMGSHj(B- (3bQGAI adSajI aj fXQjI GdeMGSHI(B- (3gjcd fXQjI GdeMGSHI(B- (3GdeaGgje GdNGUI HGdGgOGa(B- (3GdeaGgje GdNGUI HWHjYI GdhMOI GdeMGSHjI(B- (3eaGgje LhOI GdeYdheGJ GdeMGSHjI(B- (3eaGgje GdbhGFe GdeGdjI GdGSGSjI(B- (3eaGgje YfGUQ GdbhGFe GdeGdjI(B- (3GdaQhV GdeMGSHjI(B- (3GdeHGOF GdeMGSHjI(B.s
Keywords: (3GdeMGSHI GdJMdjdIs; (3GdeMGSHI(B- (3fXQjGJs